COVID-19 Crisis and Labor Migration Policy: A Perspective From Estonia - Jakobson, Mari-Liis; Kalev, Leif (Frontiers in Political Science, 2020)
Crises can function as catalysts for policy change, but change depends on multiple factors such as the actual content of the event, the agenda-setting power of the advocates of change, and their abilities to foster advocacy coalitions and break up policy monopolies. The COVID-19 crisis is an event that halted virtually all movement, including labor migration across the world, thus having great potential to act as a major focusing event. This article will look into the possibilities of this crisis to induce permanent labor migration policy change based on the case of Estonia. The article thus contributes to the literature on migration policy change from the Central and East European perspective.